Therapeutic extraction of second molars in orthodontics: a scoping review - Ziad M. Montasser; Mona A. Montasser (BMC Oral Health)
Abstract Objective To review the literature to identify the present evidence on the extraction of second molars in orthodontics. Materials & method A search of the MEDLINE/PubMed®, Scopus, Web of Science™, and ProQuest® databases for full-text articles was done on March 5, 2024. The search went back till the 1st of January 1991 and was limited to articles in English. The results of the first search went through a preliminary check to remove duplicates and then the titles and abstracts of the articles were read to exclude the irrelevant studies, case studies, or reviews. The abstracts of the selected studies were read carefully to verify if the inclusion criteria were met. Finally, the full texts of the potentially eligible studies were read to apply the eligibility criteria and decide whether to include them in the review or not. The eligibility criteria were set following the PICO (population, intervention, comparison, and outcome) standard. The included studies were thoroughly summarized by extracting the most important information. Results The electronic search located a total of 103 articles distributed among the databases. Removing duplicates left 48 Studies. After careful assessment of the titles and abstracts, 32 studies were excluded leaving 16 studies. Applying the inclusion/exclusion criteria resulted in the exclusion of 2 studies and including 14 studies in the scoping review. Conclusions There is quite low level of evidence to support second molar extraction in orthodontics. Conducting a systematic review would not add much to the evidence as well-conducted RCTs are needed first.